A heretical tale about heresy or when words do matter - Vanhoutte, Kristof (HTS teologiese studies, 2019)
What came first, heresy or orthodoxy? Walter Bauer’s book Orthodoxy and Heresy in Earliest Christianity, published in 1934, seems to have unleashed the demons of scholars of early Christianity. Partisanship has, however, starkly coloured the still ongoing discussion. Denominational and scholarly belonging, as the work of Bart Ehrman and of his opponents like Andreas Köstenberger and Darrell Bock has widely shown, has so taken the upwind and signed this discussion that a full investigation into the meaning and the history of the concepts at hand has been ‘forgotten’. The customary and common understanding of the concepts of orthodoxy and, in particular, heresy, are, however, completely inadequate for this discussion. Ignoring the enormous cultural heritage of the concept of heresy (αἵρεσις) – which we intend to unveil in this article – has made for the word-bullets in this historical battle to turn out to be little more than blanks in a sham-war. Time has come to end this battle, which is the scope of this article.